The Role of Yoga in Managing Pain and Improving Quality of Life in Patients With Chronic Low Back Pain: A Systematic Review - Mahendra Wahyu Dewangga; Rinna Ainul Maghfiroh; Ekan Faozi; Sri Indra Kurnia; Erma Juana Ginting; Farrah Rizky Mutiara; Nur Afrina Azra; Yudha Wirajati (Balneo and PRM Research Journal, 2025)
Chronic low back pain (CLBP) remains a leading cause of disability worldwide, adversely affecting both physical function and psychological well-being. Although conventional treatments such as physiotherapy and pharmacotherapy are widely used, their long-term effectiveness is often limited. In recent years, yoga has gained attention as a complementary intervention. This systematic review aims to evaluate the effectiveness of yoga in reducing pain and enhancing quality of life among individuals with CLBP. Following PRISMA guidelines, a comprehensive literature search was conducted in PubMed and Scopus databases. Eligible studies were randomized controlled trials (RCTs) published from 2020 onward, written in English, indexed in Scopus, and focused on yoga interventions for CLBP. A descriptive synthesis was performed. Eight RCTs met the inclusion criteria. Common outcome measures included the Visual Analogue Scale (VAS) for pain intensity, the WHO Quality of Life-BREF (WHOQOL-BREF), and the 12-Item Short Form Survey (SF-12) for health-related quality of life. The findings consistently indicated that yoga significantly reduced pain, improved functional capacity, and enhanced overall quality of life. Compared to conventional physiotherapy and standard exercise programs, yoga demonstrated comparable or superior benefits, particularly in alleviating stress and promoting mental well-being. These results suggest that yoga is a safe, effective, and holistic adjunct to conventional physiotherapy for managing chronic low back pain.